UTILIZATION OF MSME DIGITAL MARKETING STRATEGIES ON INSTAGRAM DESCRIPTIVE QUALITATIVE ANALYSIS @DENISA_SPREI - Yulianti, Alin; Zaelani, Pupi Indriati; Munastha, Ketut Abimanyu; Lestari, Nina; Muzakki, Ahmad (PT Altin Riset Publishing, 2024)
This study aims to analyze the digital marketing strategies employed by micro, small, and medium enterprises (MSMEs) on Instagram, specifically focusing on the @denisa_sprei account. The research employs a descriptive qualitative approach, utilizing data collected through direct observations of the Instagram account, semi-structured interviews with the account owner, and analysis of Instagram features and performance metrics. The primary objectives are to identify the key strategies used for enhancing brand visibility, engaging with customers, and boosting sales through Instagram. The findings reveal that @denisa_sprei effectively employs several strategies to maximize its digital marketing efforts. The use of visually appealing content, including high-quality images and engaging videos, plays a crucial role in attracting customer attention and building brand identity. Active interaction with followers through comments and direct messages (DMs) strengthens customer relationships and improves loyalty while leveraging Instagram features such as Instagram Stories, Instagram Reels, and Instagram Shopping enhances customer convenience and facilitates the purchasing process. Additionally, Instagram Insights is utilized to track performance and adjust strategies based on follower preferences and engagement metrics. Overall, the study concludes that Instagram serves as a powerful marketing tool for MSMEs, providing significant benefits in terms of brand visibility, customer engagement, and sales growth. These insights offer valuable guidance for other MSMEs seeking to optimize their social media marketing strategies.